2017
DOI: 10.1038/nrm.2017.104
|View full text |Cite
|
Sign up to set email alerts
|

The functions and unique features of long intergenic non-coding RNA

Abstract: Long intergenic non-coding RNA (lincRNA) genes have diverse features that distinguish them from mRNA-encoding genes and exercise functions such as remodelling chromatin and genome architecture, RNA stabilization and transcription regulation, including enhancer-associated activity. Some genes currently annotated as encoding lincRNAs include small open reading frames (smORFs) and encode functional peptides and thus may be more properly classified as coding RNAs. lincRNAs may broadly serve to fine-tune the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
843
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,068 publications
(856 citation statements)
references
References 167 publications
(252 reference statements)
9
843
0
4
Order By: Relevance
“…Accumulating evidence have demonstrated that the function of lncRNAs could be either as an oncogene, or a tumor suppressor gene, or both involved in tumor prognosis and progression, depending on the circumstance(s) [13–15]. Amongst them, many lncRNAs, such as MALAT1, H19, and HOTAIR have been demonstrated as a critical regulator of carcinogenesis and development of many cancers [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence have demonstrated that the function of lncRNAs could be either as an oncogene, or a tumor suppressor gene, or both involved in tumor prognosis and progression, depending on the circumstance(s) [13–15]. Amongst them, many lncRNAs, such as MALAT1, H19, and HOTAIR have been demonstrated as a critical regulator of carcinogenesis and development of many cancers [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic studies have annotated tens of thousands of lncRNAs—transcripts > 200 nt in length that do not appear to code for proteins—and such lncRNAs can be mapped to every chromosome . While certain lncRNAs are now known to play key roles in critical cellular processes —such as lncRNA XIST in X chromosome inactivation —the vast majority of lncRNAs have not been demonstrated to have significant biological functions. For this emerging field of research, an important next step is to identify which lncRNAs regulate important aspects of cell and molecular biology, and lncRNA loss‐of‐function and gain‐of‐function approaches are a mainstay for such discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that lncRNAs play important roles in the different biological process such as cell growth and differentiation, apoptosis and immune responses. Indeed, deregulation of lncRNA has been associated with different human diseases, including cancer, tumorigenesis and neurological diseases . LncRNAs are predominantly found in the cytoplasm and nucleus suggesting that lncRNAs regulate cell functions in both locations.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are predominantly found in the cytoplasm and nucleus suggesting that lncRNAs regulate cell functions in both locations. Indeed, studies have shown that lncRNAs can control gene expression by epigenetic regulation and also influencing transcription factors . Several aspects of lncRNA can be exploited for therapeutic purposes because of two major advantages.…”
Section: Introductionmentioning
confidence: 99%